Comprehensive Review of Transformative Trends in Global Healthcare Practices - Alzamanan, Mohammed; Alzamanan, Saud; Alhendi, Fares; Almurdif, Rashed Saleh; AL Yami, Saleh Mansour; Alyami, Marzouq Mohammed Hussain; Alzmanan, Mana; Almudrif, Ghalib; Al Mansour, Salem; Alsarrar, Hussain (Journal of Ecohumanism, 2024)
This literature review throws the limelight on changing dynamics in global healthcare and related advancements and issues that are revolutionizing healthcare systems across the globe. Such trends include digital health technologies, patient engagement and centred models of care, telehealth or telemedicine increasing access, and health promotion and disease prevention. They identify how these changes affect all facets of the health systems, the healthcare fraternities, and care users and underscore dynamism as a critical consideration for good policy and strategies. Thus, the results provide evidence of the necessity of adapting healthcare systems to these trends and making the necessary changes to improve the availability of health services.